TEACHER'S STRATEGY IN ENVIRONING FINAL VALUES IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 IN STUDENTS MIS CHAIRUL BARIYYAH SEI SEMAYANG - Ali Imran Sinaga; Zaini Dahlan; Ajeng Endah Wulandari (Universitas Dharmawangsa Medan, 2020)
This research aims to: (1) 1. To find out how a teacher's strategy is in instilling moral values in the 4.0 industrial revolution era in MIS Chairul Bariyyah students, (2) To find out the application process carried out by the teacher in instilling the moral values of MIS Chairul Bariyyah students to become better in the era of the industrial revolution 4.0, and (3) 3. To find out the results of inculcating moral values in the era of the industrial revolution 4.0 in MIS Chairul Bariyyah students. Research findings show: (1) The teacher's strategy in instilling moral values at MIS Chairul Bariyyah Sei Semayang Sunggal is through the uswah or exemplary method, the habituation method, the hiwar or conversation method and the advice and motivation method, (2) Instilling the moral values of students at MIS Chairul Bariyyah Sei Semayang Sunggal, namely the implementation of morality towards God, the implementation of morality towards oneself, the application of morality to the family, the application of morality to society and the application of morality to the environment, and (3) According to the observations I have made during my research at MIS Chairul Bariyyah Sei Semayang Sunggal that inculcating moral values in students can fortify and change students' morals for the better. So that students can think independently and can distinguish between good deeds and bad deeds. To instill good moral values in students, religious activities are needed as explained in the discussion of the research above, namely greeting and kissing the teacher's hand, reading the Koran and memorizing short suras, praying in congregation, reading prayers before studying and other activities. other.